COMMUNICATION BEHAVIOR OF KOREAN GIRLBAND FANBOY: (Study of Dance covers Community PF Entertainment in Palembang) - Ega Divya; Reza Aprianti; M Mifta Farid (Program Studi Jurnalistik, Universitas Islam Negeri Raden Fatah Palembang, 2023)
This research is entitled